La violencia familiar y su relación con el rendimiento académico en el área ciencia tecnología y ambiente de los estudiantes del 4to grado de secundaria Germán Tejada Vela de la provincia de Moyobamba - Baca Peréy, Waldir Barbaza (2011)
Violence within the famíly caused a negative impact on íts members, if the member is a child even more. Oue to its characteristícs of fragility and because their development process is underway. At school, these consequences wíll be felt primaríly wíth evidence of an academic and behavioral negative nuances. The reflections of home violence at school wíll be felt in rates of low performance, lack of motivation during the process . and límíted behavioral manifestations against the internalization of learning, in severe situations will download the same signals received by the family violence. The research aimed to examine the educational institution German Tejada Vela of the district Moyobamba 1\nk between the presence or absence of family violence ín the fifth grade students and academic performance in a specific area such as Science, Technology and Environment, to demonstrate , from these results, the prevalence of thís link between two important variables in the teaching~learning process. On the basis ot the theory related to social and cultural conception of the family, functíons in front of hís formative role of individuals ín their structure, theoretically associated to the concept of \eaming as academic pertormance and how this evolves in the context variable of such a nexus, In the investigation the working group reached a total of 140 participants, students from the five sectíons of fifth grade to make the study reach. The investigation was restricted to a descriptiva correlational design, with the instrumental support research a questlonnaire to verify, since the perception of students, the presence or absence of violence in the homes they come from. Was complementad with a record of academic performance interval. The data ís processed and presentad in two parts, the first part takes a descriptiva character based on modal analysis, ie considering the hígher frequencies. The second part compares the two variables through a correlational analysís chí-square coefficíent, data were used primaríly to test our hypotheses thus demonstrated a probable link between the two variables considerad in the ínvestígation.